Exploring changing needs following minor stroke. (30th September 2019) - Finch, Emma; Foster, Michele; Fleming, Jennifer; Cruwys, Tegan; Williams, Ian; Shah, Darshan; Jaques, Katherine; Aitken, Philip; Worrall, Linda
Abstract: Medical advances have led to many of the severe consequences of stroke being averted. Consequently, more people are being discharged from hospital following treatment for what is classed as minor stroke . The needs of people with minor stroke have received little research attention. The aim of the current study was to conduct an exploratory prospective needs analysis to document the unmet health, rehabilitation and psychosocial needs of a recently hospitalised minor stroke cohort approximately 2 weeks (T1) and 2 months (T2) post‐hospital discharge. An exploratory cohort design was used to explore the unmet health, service and social needs of 20 patients with minor stroke. Participants completed questionnaires (Survey of Unmet Needs and Service Use, Mayo‐Portland Adaptability Inventory‐4, Exeter Identity Transition Scales, RAND 36‐Item Health Survey 1.0) at T1 and T2. Nine participants reported unmet needs at T1 and seven participants reported unmet needs at T2. Between T1 and T2, there was a significant improvement in perceived role limitations due to physical health. Participation in society was significantly better at T2. In conclusion, patients with minor stroke report health, service and social needs that are unmet by existing services. This patient cohort urgently requires co‐ordinated services to detect and manage these unmet needs.